Implementation of Scientific Approach to Increasing Junior High School Students' Mathematical Problem Solving Ability - Nurlina, Arni; Hendriana, Heris; Fitrianna, Aflich Yusnita; Afrilianto, Muhammad (IKIP Siliwangi, 2024)
This research aims to analyze the learning of class VIII students at Nur Al Rahman Middle School in Cimahi City on linear equations of two variables system material using a scientific approach. In learning mathematics using a scientific approach, especially in linear equations of two variables system material, it is hoped that students can play an active, creative, skilled, and noble character, find and solve problems. The research method used was classroom action research with the subjects studied being 15 class VIII students. This research was conducted for 2 cycles with data collection techniques, namely observation, documentation, and tests in the form of essays that match the indicators of mathematical problem-solving ability. The increase in students' mathematical problem-solving abilities can be seen from the achievement of the percentage of test questions on the problem-solving abilities of the 2 cycles carried out. The instrument used in the research results found that the problem-solving ability skills in linear equations of two variables system material were 33% for cycle I, then 80% in cycle II. This means that learning mathematics in linear equations of two variables system material using a scientific approach has a better influence on students' mathematical problem-solving.